Building a medical workforce in Tasmania: A profile of medical student intake. (4th February 2019) - Cheek, Colleen; Hays, Richard; Allen, Penny; Walker, Gary; Shires, Lizzi
Abstract: Objective: To identify under‐represented groups in a medical school intake. Design: Descriptive analysis of student demographic characteristics. Setting: One state‐wide medical school. Participants: All students enrolled between 2010 and 2016. Main outcome measure(s): Proportion of students from regional and rural areas, state versus independent schools, highest parental qualification, Aboriginal or Torres Strait Islander students. Results: Of 819 students, 472 (57.6%) were from Tasmania, five (1.1%) identified as Aboriginal or Torres Strait Islanders, 335 (71.0%) completed their secondary education at independent schools and 137 (29.0%) at government schools. The overall median Modified Monash Model was 2 (range 1–6) and median Australia Statistical Geography Standard Remoteness Area was 2 (inner regional: range 1–4), reflecting that a majority came from one of the two main cities. Over two‐thirds (69.5%) had a parent with a Bachelor degree or higher qualification, regardless of the school attended. Just under half (225, 47.7%) of all Tasmanian students attended a secondary school with a parental contribution of ≥5000 per annum. These students attended a small number of independent schools, with the proportion relatively stable over the period from 2010 to 2016. Conclusion: Widening participation and widening access initiatives to graduate doctors who understand and want to work in communities in need might not be working as well in Tasmania as elsewhere in Australia. Social accountability might be improved by adapting a rural classification that reflects the demographic profile of Tasmania.